2019
DOI: 10.1111/jphp.13141
|View full text |Cite
|
Sign up to set email alerts
|

A potential risk factor for paraoxonase 1: in silico and in-vitro analysis of the biological activity of proton-pump inhibitors†

Abstract: Objectives Proton‐pump inhibitors (PPIs) are drugs commonly utilized by about 7% of adults in the world. Recent researches have shown that there are countless and severe side effects of these drugs. This situation has raised concern among clinicians and patients alike. The purpose of this study is to contribute the novel drug discovery and development technology and toxicology field by researching interactions of PPIs on paraoxonase 1. Methods In this study, the paraoxonase 1 enzyme was purified from human ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 87 publications
0
31
0
Order By: Relevance
“…[73] The ligands were optimized in the OPLS3e force field [74] using the LigPrep module. [75] The boxes enclosing the centroid of cocrystallized ligands (CJK, 53X, AA7, and N0J, respectively) were set as the grid by Receptor Grid Generation [76] in Maestro. Ligands were docked with the extra precision mode (XP) [77] of Glide, and the poses showing the highest docking score values and suitable binding interactions were subjected to an MM-GBSA (molecular mechanics/generalized Born surface area)-based refinement [78] in the Prime module.…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…[73] The ligands were optimized in the OPLS3e force field [74] using the LigPrep module. [75] The boxes enclosing the centroid of cocrystallized ligands (CJK, 53X, AA7, and N0J, respectively) were set as the grid by Receptor Grid Generation [76] in Maestro. Ligands were docked with the extra precision mode (XP) [77] of Glide, and the poses showing the highest docking score values and suitable binding interactions were subjected to an MM-GBSA (molecular mechanics/generalized Born surface area)-based refinement [78] in the Prime module.…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…The molecular docking analyses were performed to affirm the binding characteristics of isoindole‐1,3‐dione substituted sulfonamides ( 3, 4 a – k ) on hCA isoforms I, II and AChE receptors. Firstly, docking parameters and prepared grids were validated by re‐docking the native ligands 2,3,5,6‐tetrafluoro‐4‐(propylsulfanyl)benzenesulfonamide (C 9 H 9 F 4 NO 2 S 2; 3TV), 4‐[(4,6‐dimethylpyrimidin‐2‐yl)thio]‐2,3,5,6‐tetrafluorobenzenesulfonamide (C 12 H 9 F 4 N 3 O 2 S 2 ; V50), and 1‐benzyl‐4‐[(5,6‐dimethoxy‐1‐indanon‐2‐yl)methyl]piperidine (C 24 H 29 NO 3 ; E20) into respective grids of hCA I, II, and AChE, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular docking analyses [46][47][48][49][50][51] were performed to affirm the binding characteristics of isoindole-1,3-dione substituted sulfonamides (3, 4 a-k) on hCA isoforms I, II and AChE receptors. Firstly, docking parameters and prepared grids were validated by re-docking the native ligands 2,3,5,6-tetrafluoro-4-(propylsulfanyl)benzenesulfonamide (C 9 H 9 F 4 NO 2 S 2; 3TV), [52] 4- Table 5.…”
Section: Molecular Docking Studymentioning
confidence: 99%
“…We also indicated that moxifloxacin hydrochloride had competitive, whereas the others showed non‐competitive inhibition . Also, in our other studies, we selected the drugs, such as diverse nucleoside analogs (gemcitabine hydrochloride, acyclovir, and 5‐fluorouracil), some calcium channel blockers (nifedipine, nitrendipine, isradipine, and amlodipine besylate), various antineoplastic medicates (palonosetron hydrochloride, bevacizumab, and cyclophosphamide), several chemotherapeutic agents (vincristine sulfate, epirubicin hydrochloride, and doxorubicin hydrochloride), some gadolinium‐based contrast agents (gadoteric acid, gadopentetic acid, gadoxetate disodium, and gadodiamide), and certain proton‐pump inhibitors (pantoprazole, omeprazole, and esomeprazole) for investigation of inhibition effects against human serum PON1 activity. We determined that most of these drugs used in the tests, despite being at therapeutic doses, inhibit PON1 strongly by exhibiting different types of inhibition mechanisms.…”
Section: Resultsmentioning
confidence: 99%